Osteogenic differentiation of two distinct subpopulations of human adipose-derived stem cells: an in vitro and in vivo study - Rada, Tommaso (2012)
The first stem cells considered for the reconstruction of bone were bone marrow mesenchymal stem cells (BMSCs). Subsequently, cells with similar marker expression panel and differentiation potential were found in new sources of cells, such as adipose tissue. This source of stem cells has a promising future in tissue-engineering applications, considering the abundance of this tissue in the human body, the easy harvesting and the high number of stem cells that are available from such a small amount of tissue. The isolation of the adipose stem cells is generally performed by means of enzymatic digestion of the tissues, followed by a natural selection of the stem cells based on their capacity to adhere to the culture flasks, leading to a quite heterogeneous population. This constitutes a major drawback for the use of these cells, since the heterogeneity of the cell culture obtained can compromise their proliferation and differentiation potential. In the present study we have analysed the in vitro and in vivo behaviour of two selected subpopulations with high osteogenic potential. For this purpose, ASCsCD29+ and ASCs STRO−1+ subpopulations were isolated and in vitro cultured onto a biodegradable polymeric scaffold, using osteogenic medium, before implantation in a nude mice model. The biodegradable polymeric scaffold used is a fibre-mesh structure based on a blend of starch and polycaprolatone (SPCL) that has been successfully used in several bone tissue-engineering studies. The implanted ASCs–scaffold constructs promoted the formation of new bone tissue in nude mice. However, the results obtained show differences in the behaviour of the two ASCs subpopulations under study, particularly regarding their potential to differentiate into the osteogenic lineage, and allowed the identification of ASCs STRO−1+ as the best subpopulation for bone tissue-engineering applications.